2021
DOI: 10.3389/fonc.2021.745092
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sphingolipids for Cancer Therapy

Abstract: Sphingolipids are an extensive class of lipids with different functions in the cell, ranging from proliferation to cell death. Sphingolipids are modified in multiple cancers and are responsible for tumor proliferation, progression, and metastasis. Several inhibitors or activators of sphingolipid signaling, such as fenretinide, safingol, ABC294640, ceramide nanoliposomes (CNLs), SKI-II, α-galactosylceramide, fingolimod, and sonepcizumab, have been described. The objective of this review was to analyze the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 234 publications
(214 reference statements)
1
51
0
Order By: Relevance
“…Moreover, since the membrane’s fluidity and ability to adapt to dynamic changes is associated with changes in lipid composition, changes in membrane composition may be an indicator of ongoing carcinogenesis [ 47 ]. It has previously been reported that, apart from changes in the phospholipid content, neoplasms also exhibit alterations in their sphingolipid content [ 42 , 48 ]. In our study, the HGG samples showed significantly decreased levels of SM 42:1;O2; however, the biochemical analysis of this observation may be vague due to the detection of only one sphingolipid showing statistically significant change ( Table S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since the membrane’s fluidity and ability to adapt to dynamic changes is associated with changes in lipid composition, changes in membrane composition may be an indicator of ongoing carcinogenesis [ 47 ]. It has previously been reported that, apart from changes in the phospholipid content, neoplasms also exhibit alterations in their sphingolipid content [ 42 , 48 ]. In our study, the HGG samples showed significantly decreased levels of SM 42:1;O2; however, the biochemical analysis of this observation may be vague due to the detection of only one sphingolipid showing statistically significant change ( Table S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are contradicting reports in the literature on the effect of SM on cancer cells. Both pro-tumor and anti-tumor properties have been reported in different types of cancer [39,42,78]. A study by Yan et al, demonstrated that in a triple-negative breast cancer mouse model, SM inhibited the proliferation and metastasis of cancer cells by reversing the polarization of M2 macrophages in tumors [79].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a more recent study identified SMs as key secreted factors that possess natural cancer-suppressing mechanisms [38]. In vivo, Cer is converted to SM by the addition of a phosphorylcholine headgroup by SM synthase [39], while sphingomyelinase can reduce the levels of SM by conversion of SM to ceramide (Cer) [40,41]. Tumor progression has been linked to a disturbed metabolic balance of SM and Cer [42].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, preclinical use of acid sphingomyelinase which cleaves the sphingolipid or sphingomyelin into ceramide has been demonstrated in cancer therapy (126). In addition, molecules such as fenretinide, safingol, ABC294640, ceramide nanoliposomes (CNLs), SKI-II, a-galactosylceramide, fingolimod and sonepcizumab that modulating sphingolipid signaling have been exploited to induce cancer cell death through apoptosis or autophagy dependent manners (127). However, it remains unclear to what extent cancer cells exhibit dependency on extracellular sphingolipids, since sphingolipids imported from fetal calf serum in vitro are entirely catabolized by cultured cells and the role of sphingolipid-transporting proteins as cancer therapeutic targets remains elusive (128,129).…”
Section: Lipidsmentioning
confidence: 99%